Novel bio-catalytic degradation of endocrine disrupting compounds in wastewater - P, Budeli; JO, Unoufin; Moropeng, Resoketswe Charlotte; Momba, MNB (Frontiers in Bioengineering and Biotechnology, 2022)
Against the backdrop of towering ecological health implications of estrogen pollution and the inefficacies associated with cost-intensive treatment techniques, this study recorded the earliest attempt of developing an inexpensive laccase-based composite for biodegradation of EDCs (Endocrine disrupting compounds), particularly estrogens. First, a central composite design was used to investigate the interactive effects of pH (6.0–8.0), inoculum size (100 – 500 U/mL), and copper (Cu) (25 – 75 mg/L) on laccase activity and estrogen degradation respectively. Thereafter, biocatalysts was synthesized comprising laccase and glass beads or silver impregnated clay granules (SICG), which was further used to treat estrogen infused aquatic matrices under different reaction conditions. Maximum laccase activities and estrogen removal for the two tested laccases were 620 U/mL (85.8 to 92.9 %) and 689.8 U/mL (86.8 to 94.6 %) for Lysinibacillus sp. BP1 and Lysinibacillus sp. BP2, respectively, within 72 h, under conditions of optimal inoculum size and/or Cu concentration. Apart from a higher estrogen removal rate compared to free laccased, the biocatalysts were more resistant to temperature, pH and other environmental perturbations, and had enhanced storage ability and reusability. In comparison to clay, beads had a higher potential for recyclability and were more stable under certain experimental factors such as pH, reuse, and temperature, as well as storage conditions. Immobilized enzymes were able to remove 100% of E2, as well as over 90% of E1 and EE2, in 24 hours, indicating that they could be scaled up to benchtop bioreactor levels.